External Oxidant‐Free Regioselective Cross Dehydrogenative Coupling of 2‐Arylimidazoheterocycles and Azoles with H2 Evolution via Photoredox Catalysis. Issue 17 (11th July 2018) - Chen, Hong; Yi, Hong; Tang, Zilu; Bian, Changliang; Zhang, Heng; Lei, Aiwen
Abstract: In this work, we achieved a site‐selective amination of 2‐arylimidazoheterocycles on the C3 position using photo‐induced external oxidant‐free strategy. The C−N bond formation with H2 evolution was realized via the oxidative C−H/N−H coupling. This protocol may have significant implications in the late‐modification of complicated drug molecules. In addition, we also used CV and DFT calculations to study the mechanism, which showed that the arene radical cation played an important role in accelerating the C−H amination process. Abstract :